Internet Use Patterns, Internet Addition, and Anxiety among Youths in Jordan: A Cross-Sectional Study - Abeer Alzayyat; Abdulkarim Alzayyat; Bassam A. Malkawi; Sajeda Al-Smadi; Siham M. Al-Momani; Jumanah D. Al-Shawabkeh (Jordan University of Science and Technology, 2024)
Background: Despite the numerous benefits of internet use, improper internet utilization may produce many psychological illnesses such as internet addiction (IA). Youths are considered vulnerable population for IA. Objectives: This current study is conducted to determine the prevalence of IA among youths in Jordan. Methods: This study employed a cross-sectional descriptive approach. The final sample consisted of 405 Jordanian youths. The researchers recruited the study participants from two universities and four schools located at different locations in Jordan. This study utilized a self report questionnaire composed of four sections; Basic Information Questionnaire, Internet Use Patterns Questionnaire, IA Test, and Generalized Anxiety Disorder Assessment. Ethical principles of nursing research were adhered. The study occurred during second semester of 2023-2024 academic year. Descriptive and inferential statistics were used for data analysis. Results: The study results revealed that about third of the participants (n= 121, 29.9%) met the criteria for IA. While there are variability among the study participants regards their online activities, social media was the main online activity (66.4 %). The study results also reported that there is a positive association between anxiety and IA (r = 0.66; p = 0.001). Conclusions: From a Jordanian viewpoint, this study adds to the understanding of the IA among youth in the international literature. To mitigate the negative effects of IA, stakeholders must work together interdisciplinary and with concerted effort. Implications for Nursing. Nurses can play an important role in raising awareness about IA among youths and make referral for the affected individuals.